Optimalisasi Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Bisnis Online dan Pengelolaan Keuangan Digital untuk Meningkatkan Pendapatan Keluarga - Muhammad Syahrizal; Dian Purnama Sari; Hablil Ikhwana; Syamsul Bahri; Vina Winda Sari (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service program aimed to improve the ability of housewives to utilize online business and digital financial management as an effort to increase family income in Medan City. The main problems faced by the participants were low digital literacy, limited use of social media and marketplaces for business marketing, and inadequate financial management of household businesses. The implementation method used a participatory approach consisting of initial observation, identification of partner needs, online business training, digital financial management training, practical sessions, mentoring, and program evaluation. The participants consisted of 20 housewives managing micro and small household businesses in culinary, fashion, handicraft, and cosmetic sectors. The results showed an improvement in participants’ digital capabilities after participating in the training, where most participants were able to use social media and marketplaces as business marketing tools. In addition, participants also began to understand the importance of financial recording and the use of simple digital financial applications in managing household businesses. Participant satisfaction with the program was also positive because the training materials were considered relevant to their business needs and easy to implement in daily business activities. This community service program is expected to become a model for women’s economic empowerment based on digital technology to support sustainable family welfare improvement.